2015
DOI: 10.1111/1365-2664.12538
|View full text |Cite
|
Sign up to set email alerts
|

Subordinate plants sustain the complexity and stability of soil micro‐food webs in natural bamboo forest ecosystems

Abstract: Summary Subordinate plants have a significant impact on soil organisms in primary successional floodplains and grassland ecosystems, but their role in subtropical forest ecosystems remains unclear. An experiment was conducted in a subtropical forest to test the hypothesis that removal of shrubs or subordinate arbour tree species would reduce the complexity and stability of the soil micro‐food web. Principal response curves (PRCs) were performed to assess the responses of soil microbial and nematode communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 57 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…Given their ability to fixed N, legumes are the most common species that consistently influence soil nematodes27. Although a recent study argues that neighboring plant diversity increases nematode diversity, abundance and resistance17, the role of legumes as a key species in plant communities is well established. Likewise, our study provides evidence that legume addition significantly enhanced bacterivores in the G. max mixed culture and tended to increase omnivore-predator nematodes in the M. sativa mixed culture (p = 0.064) when compared to the monoculture (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given their ability to fixed N, legumes are the most common species that consistently influence soil nematodes27. Although a recent study argues that neighboring plant diversity increases nematode diversity, abundance and resistance17, the role of legumes as a key species in plant communities is well established. Likewise, our study provides evidence that legume addition significantly enhanced bacterivores in the G. max mixed culture and tended to increase omnivore-predator nematodes in the M. sativa mixed culture (p = 0.064) when compared to the monoculture (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the effects of the composition of plant species in increasing the uptake of nutrients for the focal species via soil food-web stability15. In theory, the presence of different plant species (especially the presence of legumes) with different above-and belowground functional traits could potentially increase soil food-web complexity and stability1617. However, stronger competition among different species may also decrease the stability of the soil food web under extreme rainfall, even in the presence of a legume10.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have documented how livestock grazing changes plant communities (Bai et al, 2012;Milchunas & Lauenroth, 1993) and soil physicochemical properties (Semmartin, Bella, & Salamone, 2009;Zhou et al, 2017). As part of soil detrital food webs, soil micro-food webs mainly include soil microorganisms (e.g., bacteria and fungi), microbivores (e.g., bacterial-feeding (BF) and fungal-feeding (FF) nematodes), and micropredators (e.g., omnivorous and carnivorous nematodes; Lavelle, 1997); these organisms contribute to the decomposition of soil organic matter and soil C and N mineralization (Lavelle, 1997;Shao et al, 2016). Several recent studies have reported that livestock grazing can greatly affect soil micro-food webs in grassland ecosystems (Veen, Olff, Duyts, & Putten, 2010;Yang, Nolte, & Wu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Abundance and diversity of nematodes are correlated with many geochemical processes such as ecosystem succession, litter decomposition and N cycling (Fu et al 2000;Neher et al2012;Zhao et al 2012). Several related studies have shown that the development and characteristics of nematode communities were greatly affected by plant community characteristics (Li et al 2007;de la Peña et al 2016;Shao et al 2016;Zhao et al 2019). Because nematodes are sensitive to external disturbances (e.g., land-use change and environmental pollution) and nematode communities are generally regarded as effective indicators of the health and stability of soil food webs (Bongers 1990;Powell 2007;Zhao et al 2013).…”
Section: Introductionmentioning
confidence: 99%